Determination of atomic vacancies in InAs/GaSb strained-layer superlattices by atomic strain. (2018) - Kim, Honggyu; Meng, Yifei; Kwon, Ji-Hwan; Rouvierec, Jean-Luc; Zuo, Jian Min
No abstract available